2012
DOI: 10.1021/am301484s
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Capacitor Electrode Based on Porous Carbon Spheres Hybrided with Polyaniline and Nanoscale Ruthenium Oxide

Abstract: Nanoscopic ruthenium oxide (RuO(2))/polyaniline (PANI)/carbon double-shelled hollow spheres (CS) composites, RuO(2)/PANI/CS, have been prepared via electro-polymerization of aniline and redox deposition of RuO(2) on the surface of CS. The structures and morphologies of the resulting ternary composites are characterized using scanning electron microscopy (SEM), infrared spectroscopy (IR), energy-dispersive X-ray spectroscopy (EDX). The electrochemical properties of the ternary composites as active electrode mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…Very similar trends were revealed for PPy nanotubes having an ultrathin coating of RuO 2 on their surface [307]. Ternary composites have also been fabricated by depositing both the CP and RuO 2 on high surface area carbon substrate [162,264]. In another study, both the inner and outer surfaces of PEDOT nanotubes were decorated with RuO 2 NPs.…”
Section: A N U S C R I P Tsupporting
confidence: 52%
See 1 more Smart Citation
“…Very similar trends were revealed for PPy nanotubes having an ultrathin coating of RuO 2 on their surface [307]. Ternary composites have also been fabricated by depositing both the CP and RuO 2 on high surface area carbon substrate [162,264]. In another study, both the inner and outer surfaces of PEDOT nanotubes were decorated with RuO 2 NPs.…”
Section: A N U S C R I P Tsupporting
confidence: 52%
“…Subsequently, RuO 2 was formed inside the nanotubes through potential cycling; more precisely, RuO 2 was electrodeposited on the inner walls of the polymeric tubes [263]. RuO 2 electrodeposition was achieved on PANI films as well, both under potentiodynamic [264] and galvanostatic [265] conditions. In the same vein, MnO 2 was hybridized with PANI [266], PEDOT [267], PMT [268] and even PEDOT-PANI assemblies [269].…”
Section: Figure 15mentioning
confidence: 99%
“…145 F/g was obtained at same scan rate of 5 mV/s for CNH. Many researchers [32,33] have reported that the capacitance value of the composites can increase due to the deposition of metal oxides or metal salts [RuO 2 or Ni(OH) 2 ] on reduced graphene oxide (RGO) sheets or by preparing thin films of PANI fibers and RGO sheets [34]. This high capacitance value of the composites is obtained due to contributions of the conducting RGO sheets and the pseudo-capacitance of the metal oxides or conducting polymer.…”
Section: Cyclic Voltammetry (Cv) Analysismentioning
confidence: 99%
“…The synthesized electrodes yielded a significantly improved volumetric capacitance of 246 F cm −3 with good capacity retention up to 1000 mV s −1 , as a results of the rapid transport of electrons and ions within the electrodes . RuO 2 /polyaniline (PANI)/carbon double‐shelled hollow sphere (CS) composites (RuO 2 /PANI/CS), synthesized through the electropolymerization of aniline, were also reported . In ECs, the SC of the RuO 2 /PANI/CS composites was 531 F g −1 at 1 mA cm −2 in a 1.0 m H 2 SO 4 electrolyte; this value exceeded that of many other currently available ternary composites based on RuO 2 /PANI.…”
Section: Introductionmentioning
confidence: 99%